Age of diagnosis, service access, and rights of autistic individuals in Argentina: Caregivers reports of changes and similarities across time - Montenegro, Maria Cecilia; Bernal, Estefani; Cukier, Sebastian; Valdez, Daniel; Rattazzi, Alexia; Garrido, Gabriela; Rosoli, Analia; Silvestre Paula, Cristiane; Garcia, Ricardo; Montiel-Nava, Cecilia (Frontiers in Psychiatry, 2022)
Background Many countries have developed health initiatives to protect those with disabilities and developmental concerns in the past few years. However, the needs of autistic individuals are still short of being fulfilled. Partially due to limited research expenditure, which would allow bridging the gap between evidence and practice, the long time it takes to implement passed laws, and the limited operationalization of inclusive policies. Objective To quantitatively examine changes in the child’s age at the time of caregiver’s first developmental concerns and age of diagnosis of their autistic child across five years. Also, to address challenges experienced by caregivers and the work still needing to be done in Argentina based on caregivers’ reports of their priorities. Methods Two independent samples of caregivers of autistic individuals were surveyed by the Red Espectro Autista Latinoamerica (REAL) in 2015 (n=763) and the World Health Organization (WHO) in 2020 (n=422). Similar items in both surveys were compared through descriptive inferential analysis and chi-square tests for categorical variables. Results Compared to the 2015 sample, for the 2020 sample, more caregivers reported an earlier age of first concerns and an earlier age of a professional diagnosis, more children diagnosed before the age of three had a doctor or a teacher noticing the first developmental concern, and fewer caregivers reported service barriers. However, rates of caregivers indicating a need for more rights for autistic individuals and greater protection of existing rights increased. For both samples, there was statistically significant differences in individual (physician, teacher, caregiver) noticing first developmental concern and the age of diagnosis, with the majority having a caregiver noticing the first concern. Conclusions The five years that separate both samples show an improvement in developmental concern being noticed, a decrease in the age of diagnosis, and an improvement in several services areas such as community awareness and fewer barriers to access services. These results suggest that the changes in public policies and advocacy work might have impacted access to services. These results imply that despite better care pathways in Argentina, there are still gaps to meet the needs of autistic individuals and their families.